Saling Jaga Atas Pelecehan Seksual di Tempat Publik - Zenny Rezania Dewantary; Anathasia Citra; Fransiska Rachel; Abhirama SD Perdana (ACADEMICS IN ACTION Journal of Community Empowerment, 2020)
Sexual harassment is still considered irrelevant to voice, let alone to fight for. People tend to put more concerns on family honor, and even consider sexual harassment as a shameful act and degrading their family’s name. Apart from at home, sexual harassment also often occurs in public places—public transportation, workplaces, schools, and other public facilities. Saling Jaga is a forum that voices concerns on sexual harassment that occurs in public spaces, and is the result of a collaboration amongst 3 undergraduate programs, (1) Law, (2) Communication Studies, and (3) Visual Communication Design, at President University. Saling Jaga forms a team that is hailed as Guardians. The purpose of this movement is to raise the awareness of everyone who witnesses sexual harassment in public places and has the courage to look after each other (bystander intervention) through activities in the form of socialization on Instagram social media, exhibition installations, and seminars to secondary schools in Kuningan.